Upregulation of a kinase interacting protein 1 in tongue squamous cell carcinoma correlates with lymph node metastasis and poor overall survival. Issue 14 (9th April 2021) - Sun, Ying; Shi, Guang; Ma, Chao; Jiao, Jianjun; Liu, Yingqi; Gao, Qingling; Zhang, Xueqiang; Feng, Qiang
Abstract : Abstract: A kinase interacting protein 1 (AKIP1) is upregulated in cancer cells/tissues and associated with deteriorative tumor features, while it has not been investigated in tongue squamous cell carcinoma (TSCC). The goal of this study was to measure AKIP1 expression and analyze its correlation with clinical feature and prognosis in TSCC patients. We retrospectively reviewed 194 TSCC patients, whose formalin fixed paraffin-embedded (FFPE) tumor tissue specimens and paired adjacent tissue specimens were accessible for AKIP1 detection by immunohistochemistry (IHC). Whereas only 107 patients whose fresh-frozen tumor tissue and paired fresh-frozen adjacent tissue that were still available in storage were included for AKIP1 mRNA detection by real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR). AKIP1 expression (both the protein detected by IHC and mRNA detected by RT-qPCR) was higher in TSCC tissue than that in adjacent tissue. In addition, both tumor AKIP1 mRNA and protein expressions were correlated with advanced N stage and TNM stage, while they were not correlated with other clinical features in TSCC patients. As for survival, there was a correlation of AKIP1 mRNA with poor overall survival (OS), while the correlation of AKIP1 protein expression with OS was of limited statistical significance. There is an upregulation of AKIP1 in TSCC and it correlates with lymph node metastasis as well as unfavorable prognosis in TSCC patients.